Estudo pré-clínico do perfil farmacocinético, biodistribuição e atividade antifúngica de formulação lipossomal de voriconazol para uso intravenoso em infecções sistêmicas - Veloso, Danillo Fabrini Maciel Costa (2018)
Voriconazole, a second-generation triazole with a large spectrum of action is one of the most recommended systemic antifungal agents as the first line therapy against several clinically important fungal pathogens, among them Candida albicans. This antifungal has moderate water solubility and exhibits a nonlinear pharmacokinetic profile due to metabolic clearance saturation. By entrapping voriconazole into liposomes it is possible to circumvent its physico-chemical limitations, avoid the high toxicity of the antimicrobial, caused by sulfobutyl ether-betacyclodextrin, vehicle used to increase its solubility, present in its commercially available formulation: VFEND®. Pharmacokinetics and biodistribution of voriconazole modified by encapsulation in liposomes allowed its antifungal activity to be potentiated, leading to increased specificity and tissue penetration, protection the drug from biological degradation and reduced metabolism. Liposomes entrapping voriconazole (LVCZ) showed a particle size of 95.3 ± 1.27 nm, PdI of 0.09 ± 0.01, zeta potential near to neutrality, as well as a high efficiency of encapsulation of the antifungal and vesicles presenting spherical morphology uni and/or multilamellar. In vitro and in vivo evaluations of the performance of the liposomal formulation containing voriconazole were all performed in a comparative fashion with the commercially available formulation, VFEND®. In the in vitro assays using different species of fungal isolates of Candida and Aspergillus sp. the liposomal formulation was equivalent or superior to VFEND®. In a non-clinical pharmacokinetic assay in Balb/c mice, using a dose of 10 mg/kg, the main pharmacokinetic parameters were obtained: Cmax (μg/mL) = 1.23 ± 0.28 and 0.61 ± 0.15; AUC0-24 (μg/ml*h) = 4.86 ± 1.01 and 1.96 ± 0.30; Cl (mL/h) = 52.75 ± 8.88 and 100.91 ± 20.14; Vd (mL) = 230.18 ± 53.61 and 314.18 ± 106.24 for LVCZ and VFEND®, respectively. In all calculated/observed parameters, the liposomal formulation presented superior performance, using the same dose as the commercial formulation. Increases in antifungal concentrations found in blood, liver and kidneys and lower amounts of the inactive metabolite formed when using the liposomal formulation can be attributed to the ability of liposomes to alter the pharmacokinetics and biodistribution of voriconazole in the body mainly because of their capacity to protect the drug from accelerated metabolism. In vivo efficacy evaluation of voriconazole was also performed in a systemic candidiasis model in immunosuppressed animals, as well as parameters such as weight loss, fungal burden in the liver and kidneys and histological alterations caused by infection and treatment. As a consequence of voriconazole pharmacokinetics and biodistribution modified by the encapsulation in liposomes, the antifungal activity of drug was potentiated, leading to greater specificity and tissue penetration. In conclusion, in order to provide appropriate dose regimens for the treatment of systemic fungal infections, avoiding obstacles such as toxicity and resistance mechanisms we developed na alternative therapeutic platform, able to lead to safe and effective treatment.